Implementation, Challenges and Opportunities of the Special Program For Employment of Students (SPES) in a First-Class Philippine Province: An Explanatory Sequential Inquiry - Bachita, Elma B.; Caelian, Merlita V. (Philippine Social Science Journal, 2025)
Targeting the intersection of education and employment under the Sustainable Development Goals, this study assessed the implementation, challenges, and opportunities of the Special Program for Employment of Students (SPES) managed by Public Employment Service Offices (PESO) in a first-class province in Central Philippines. The research utilized an explanatory sequential mixed-method design, integrating quantitative data from students selected through stratified random sampling with qualitative insights from experienced PESO implementers chosen via purposive sampling. Results indicated a highly effective implementation of SPES across various local government units, with beneficiaries reporting significant economic and social benefits that facilitate access to education and reduce unemployment. Although challenges persist, the findings highlight the critical role of PESO and provide a strategic baseline for the Department of Labor and Employment (DOLE) and Local Government Units (LGUs) to enhance program delivery, contribute to SDGs 1 and 8, and guide future research on integrating local livelihood programs.